Design and Realization of Compact Microstrip Antenna Using Fractal Sierpenski Carpet For Wireless Fidelity Application - Syah Alam; Indra Surjati; Awang Ferawan; Teguh Firmansyah (IAES Indonesian Section, 2018)
This paper proposed new design of compact microstrip antenna using fractal sierpenski carpet method for Wireless Fidelity application at working frequency of 2400 MHz. The proposed antenna using FR4 Epoxy with (εr) of 4.3, substrate thickness (h) of 1.6 mm and loss tangent (tan δ) of 0.0265. Antenna is designed using AWR Microwave Office software.The sierpenski carpet method is used in order to reduce the dimensions of the microstrip antenna to become more compact. From the measurement results obtained reflection coefficient value -26.077 dB, VSWR 1.104 at working frequency of 2400 MHz frequency with a bandwidth of 127 MHz (2338 MHz – 2465 MHz). Beside that, by using fractal sierepenski carpet method, microstrip antenna dimension was reduced until 47.80% compared to conventional rectangular microstrip antenna.